Pengaruh Brand Ambassador dan Kualitas Produk Terhadap Niat Beli Produk Scarlett di Shopee - Hariyanto, Alycia Najwa; Kusuma2, Putu Sri Arta Jaya (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
In the modern era, human needs for health and beauty continue to rise rapidly, driving fierce market competition in the beauty industry. Marketers must also innovate and deliver creative and exciting products to compete with local and foreign products. The first step in caring for the skin's health and appearance is to use skin care products. Scarlett Whitening has become a popular choice among consumers with its good reputation. This research and data on the number of customers of Scarlett whitening at Shopee suggests that brand ambassadors play a crucial role in increasing product sales and consumer confidence. In addition, the brand embassy positively affects consumer interest in purchasing Scarlett products at Shopee. Beauty product sellers preferably apply this strategy to increase sales and their market share.